Use Of Simple Spectrophotometric Method For Estimation Of Theophylline (TH) In Saliva And Urine Of Healthy Human Volunteer - VIKAS KUMAR; ARVIND SHARMA; SANDEEP ARORA; VIPASHA DHILLON (International Journal of Pharma and Bio Sciences, 2011)
A simple and sensitive spectrophotometric method was developed and validated for the determination of Theophylline (TH) in pharmaceutical dosage form as well as in human saliva and urine samples. This method is based on the measurement of absorbance of TH in Phosphate Buffer 6.8 at 270 nm. Beer’s law is obeyed over the range of 2-10 μg/ml. This method was used successfully for the quality assessment of Theophylline drug in human urine and saliva samples with good precision and accuracy. The Sandell sensitivity, limit of detection (LOD) and limit quantification (LOQ) values are also reported. All the methods were validated in accordance with current ICH guidelines. The developed methods were employed with high degree of precision and accuracy for the estimation of total drug content in commercial tablet formulations of TH. The results obtained from human spiked urine and saliva are satisfactory and recovery values were in limits.